I-Love-Q relations for neutron stars with dark energy - Simone D’Onofrio (European Physical Journal C: Particles and Fields)
Abstract The influence of a dark energy fluid on the equation of state of neutron stars is investigated. A detailed analysis is conducted for such models, including the computation of the moment of inertia, the quadrupole moment, and the tidal Love number. The results demonstrate that these quantities are interconnected through the well-known equation of state independent I-Love-Q relations. This work extends the applicability of these universal relations to a broader class of neutron star models.